Neural correlates of temporal summation of second pain in the human brainstem and spinal cord. Issue 12 (14th September 2015) - Bosma, Rachael L.; Ameli Mojarad, Elham; Leung, Lawrence; Pukall, Caroline; Staud, Roland; Stroman, Patrick W.
Abstract: Temporal summation of second pain (TSSP) occurs when painful stimuli are presented repetitively (≥0.33 Hz) and results from a C‐fibre evoked enhancement (or "wind‐up") of the dorsal horn neurons. Based on electrophysiological studies in intact animals, windup is considered a purely central phenomenon. With advancements in functional MRI (fMRI), we can now probe the central mechanisms of this pain response in humans. The aim of this study is to characterize the fMRI responses in the healthy human brainstem and spinal cord that correspond to TSSP. Functional MRI of healthy female adults ( N  = 15) was conducted while brief, repetitive heat pain stimuli were applied to the right thenar eminence (C6 dermatome), and TSSP (0.33 Hz) and control (0.17 Hz) heat pain paradigms were employed. The stimulus intensity was adjusted to each participant's heat pain sensitivity. Data were analyzed by means of a general linear model, and region‐of‐interest analyses. As predicted, participants demonstrated significant behavioural summation of pain in the TSSP condition. FMRI results identified enhanced activity in the spinal cord dorsal horn at C6 in response to the TSSP condition. Additionally, multiple areas of the brainstem (RVM and PAG) showed greater responses with the TSSP condition. These results suggest that, in humans, increased pain perception in the TSSP condition is reflected by greater responses in the dorsal horn and in regions known to play a role in the descending modulation of pain, which may modulate the spinal cord response. Hum Brain Mapp 36:5038–5050, 2015 . © 2015 Wiley Periodicals, Inc.